Association of acute tubular necrosis with gross hematuria in cirrhosis-related immunoglobulin A nephropathy - Jang Soo Han; So Dug Lim; Won Hyeok Choi; Sung Chul Hong; Jung Hee Park; Eugene Park; Mi Jin Hong; Cho I Lee; Jung Hwan Park; Jong Ho Lee; Jong Oh Song; Young Il Jo (The Korean Society of Nephrology, 2013)
Immunoglobulin A (IgA) nephropathy associated with cirrhosis is the most common form of secondary IgA nephropathy (IgAN). Cirrhosis-related IgAN is usually clinically silent with a rare occurrence of gross hematuria, unlike in cases of idiopathic IgAN. Especially, acute tubular necrosis (ATN) associated with gross hematuria is very rare in cirrhosis-related IgAN, although acute renal failure is a frequently reported complication in advanced cirrhosis. Herein, we report an unusual case of ATN requiring renal replacement therapy, associated with gross hematuria in a patient with nonalcoholic, hepatitis B virus-associated cirrhosis. Results of a histopathological analysis revealed obstruction of the lumen of renal tubules by red blood cell casts, a marked tubular necrosis, and IgA deposition in the mesangium. The patient's renal function and gross hematuria were clearly improved after lamivudine treatment.